PENGARUH CAPITAL STRUCTURE, PROFITABILITY, FIRM SIZE, GROWTH, DAN LIQUIDITY TERHADAP NILAI PERUSAHAAN - Christianto, Albert; Rasyid, Rosmita (Jurnal Paradigma Akuntansi, 2024)
This study aims to obtain empirical evidence about the effect of capital structure, profitability, firm size, growth, and liquidity on the firm value of consumer goods manufacturing companies listed on the Indonesian stock exchange for the 2017-2019 period. The sample used in this study was obtained using purposive sampling, consisting of manufacturing companies in the consumer goods sector listed on the stock exchange in 2017-2019. The data obtained for this study were processed using eviews9. The results showed that capital structure had a significant effect on firm value, profitability, firm size, growth and liquidity had no effect on firm value.